2001
DOI: 10.1002/rcm.361
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen isotope analysis of natural abundance and deuterium‐enriched waters by reduction over chromium on‐line to a dynamic dual inlet isotope‐ratio mass spectrometer

Abstract: This paper describes the application of a simple chromium reduction furnace which can be interfaced with a dual inlet isotope-ratio mass spectrometer thus providing the capacity for cheap, fast, accurate and precise measurement of deltaD(V-SMOW) by dynamic mass spectrometry. Measurements are precise to the order of < or =0.5 per thousand. Mean 95% confidence intervals for the Vienna Standard Mean Ocean Water (V-SMOW) to Standard Light Antarctic Precipitation (SLAP) range are in the order of 2.5 per thousand an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 12 publications
(19 reference statements)
0
50
0
Order By: Relevance
“…Oxygen isotope ratios were analysed at SUERC using an automated CO 2 equilibration technique (after Epstein and Mayeda, 1953) using 1 ml of sample and analysing the resulting equilibrated CO 2 on an Analytical Precision AP2003 continuous-flow isotope ratio mass spectrometer. Water was reduced to H 2 using a chromium furnace (Donnelly et al, 2001); this was analysed using a VG SIRA 9 mass spectrometer (2005 samples) and a VG Optima (2006 samples). Oxygen and hydrogen isotopes were measured relative to V-SMOW.…”
Section: Oxygen and Hydrogen Isotopesmentioning
confidence: 99%
“…Oxygen isotope ratios were analysed at SUERC using an automated CO 2 equilibration technique (after Epstein and Mayeda, 1953) using 1 ml of sample and analysing the resulting equilibrated CO 2 on an Analytical Precision AP2003 continuous-flow isotope ratio mass spectrometer. Water was reduced to H 2 using a chromium furnace (Donnelly et al, 2001); this was analysed using a VG SIRA 9 mass spectrometer (2005 samples) and a VG Optima (2006 samples). Oxygen and hydrogen isotopes were measured relative to V-SMOW.…”
Section: Oxygen and Hydrogen Isotopesmentioning
confidence: 99%
“…The δD m values increase with time and eventually reach a steady value after 6 min within an analytical error of 0.5‰. Life of chromium Donelly et al (2001) state that approximately 180 runs are possible using 1 µl of water per run in a reactor containing Cr of a similar amount and grain size. In our case, we found that 100~150 runs are possible using 2 µl of water per run.…”
Section: Optimum Conditions For Reductionmentioning
confidence: 98%
“…The overall configuration of the reaction tube and furnace is similar to that described by Donelly et al (2001). Our system, however, includes some improvements described here.…”
Section: Reaction Tube and Chromium Furnacementioning
confidence: 99%
See 2 more Smart Citations